Integration of Sustainable Development Goals in university STEM courses: A case study - Muhammad Azmi Nuha; Retchelle P. Sangco (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The objectives of this study are: (1) to provide an overview of the validity of learning tools for STEM Method courses based on the Sustainable Development Goals Curriculum, (2) to assess the practicality of these learning tools, and (3) to evaluate their effectiveness in enhancing students' problem-solving abilities. This research employs the Research and Development (R&D) methodology. Data collection methods include interviews, product validation, questionnaires, and tests. Data analysis techniques encompass qualitative analysis, product validity testing, practicality testing, and effectiveness testing. The findings indicate that: (1) learning tools for STEM Method courses based on the Sustainable Development Goals curriculum comprise a Learning Plan and teaching materials, both of which are highly valid (scores of 3.4 and 3.5 respectively), (2) the practicality test of the teaching materials scored 3.73, indicating high practicality, and (3) these tools effectively improve students' problem-solving abilities, as evidenced by the experimental class outperforming the control class. In conclusion, the study demonstrates that the designed learning tools aligned with the Sustainable Development Goals Curriculum not only show strong validity and practicality but also significantly enhance students' problem-solving skills in STEM education contexts.